Clinical and Epidemiological Features of Hymenolepidosis and Teniarichosis in Children - Rakhimovich, Oblokulov Abdurashid (Central Asian Journal of Medical and Natural Science, 2022)
The analysis of the distribution of patients by age showed that hymenolipidosis was registered mainly in children from 4 to 11 years (70.8%), and teniarynchosis from 16 to 18 years (48.3%). When comparing the clinical signs in the patients studied in the article, memory loss, increased nervousness, depressed mood, eyelid cramps and blinking due to astheno-vegetative symptoms were significantly higher (P <0.001) in patients with hymenolipidosis than in patients with teniarynchosis. It was reported that in patients with teniarinosis, symptoms such as weight loss, discomfort, fainting, abdominal pain and vomiting were significantly high (P <0.001).